Oscillation of the solutions of a class of impulsive differential equations with a deviating argument. (1998) - Bainov, D. D.; Dimitrova, Margarita B.; Dishliev, Angel B.
Abstract : Sufficient conditions are found for oscillation of all solutions of a class of impulsive differential equations with deviating argument.